Frontiers in geochemistry : contribution of geochemistry to the study of the earth / edited by Russell Harmon and Andrew Parker. - Harmon, R. S. (Russell S.); Parker, A. (Andrew), 1941- (Wiley-Blackwell, 2011)
"This is a unique collection of reviews of the significance of geochemistry in the earth sciences, with contributions from a range of internationally distinguished scientists. It deals with both the historical contribution (Part 1) and the current and likely future importance of the subject in dealing with key environmental issues (Part 2) The book is based on contributions given to the 2008 IGC session with same name: Provides the most comprehensive review of the scope and achievements of modern geochemistry in a form accessible to and affordable by students (advanced undergraduates and graduates) The contributors are all world leaders in their particular field Co-published with the IAGC - the worlds premiere learned society for the geochemistry community. The only affordable and single-volume overview of the entire subject."--